What lies beneath : root traits of dominant species in a primary and secondary forest in Singapore - Lee, Ming Yang (Nanyang Technological University, 2020)
Phosphorus limitation underlies many tropical ecosystems worldwide, driving plants to adopt a wide range of nutrient acquisition strategies through critical root functional traits. These traits and strategies rarely operate independently from one another and vary greatly across environmental gradients, depending on the plasticity of each trait. Previous studies have reported large magnitudes of root trait variations that span across multiple dimensions while proposing a myriad of possible drivers for these variations. However, studies on root traits in Southeast Asian tropical forests remain understudied compared to other ecosystems and it is uncertain whether Southeast Asian tropical forest tree species follow global patterns. Here, we provided data on root morphological and architectural traits of key dominant species found within a primary and an adjacent secondary forest in Singapore. Specifically, we assessed whether root functional traits align consistently with a “root economic spectrum” as proposed by previous studies. We further examined the overall root trait variation using multivariate tools to define independent trade-offs in root systems and constructed linear mixed models to test if forest successional type significantly influenced root traits. After controlling for trait differences due to species, we found that forest type had no significant effect on roots trait values and the various nutrient acquisition strategies formed. While different species possessed various combinations of root trait values to form unique acquisition strategies, there was no significant contrast in trait values that differentiated trees from either forest type. We proposed that both forest types suffer from similar degrees of nutrient limitation, thus inducing similar root trait responses despite differing species composition and land-use history. Incorporating more information regarding soil fertility, physiological traits and mycorrhizal symbiosis might aid us in furthering our understanding of root trait variations underlying similar tropical rainforests within Southeast Asia.